Unraveling the nature of nano-diamonds and silica in a catheterized tapered artery: highlights into hydrophilic traits - Sara I. Abdelsalam; M. M. Bhatti (Scientific Reports, 2023)
Abstract In this work, we observe the behavior of a hybrid nanofluidic model containing nanodiamonds and silica nanoparticles. The nanofluid propagates through a catheterized tapered artery with three distinct configurations: converging tapered, non-tapered and diverging tapered arteries. In order to assess the rheological properties of the blood, the third-grade non-Newtonian fluid is employed in the flow model such that the Newtonian versus non-Newtonian effects are revealed. The system of equations governing the flow is modeled under magnetic field and with heat transfer, then solved in a closed form using the perturbation approach for the pertinent parameters. The interpretations of the physical variables of interest, such as the velocity, temperature and wall shear stress, are explained. The integration of diamonds and silica nanoparticles give rise to diverse of biological applications since they are used in the drug delivery and biological imaging in genetic materials due to their hydrophilic surfaces. The present mathematical analysis lays a solid foundation on possible therapeutic applications in biomedicine.